CARDIOPULMONARY BYPASS-DERIVED PLASMA EXOSOMAL HMGB1 CONTRIBUTES TO ALVEOLAR EPITHELIAL CELL NECROPTOSIS VIA mtDNA/CGAS/STING PATHWAY. Issue 6 (3rd December 2022) - Zhao, Yupeng; Zhang, Jinyuan; Lu, Huihong; Mao, Yiliang; Qin, Jiawen; Wang, Yinglin; Wang, Xuebin; Dai, Zhiguang; Wang, Xiangrui; Yang, Zhongwei; Hou, Lei
ABSTRACT: Our previous study confirmed that cardiopulmonary bypass (CPB) leads to acute lung injury (ALI) via inducing high-mobility group box 1 (HMGB1) release. Recent research showed that HMGB1 promotes pulmonary injury mainly via exosomes transport. Currently, alveolar epithelial cell (AEC) necroptosis has been demonstrated to be involved in ALI. However, it is unknown whether exosomal inflammatory cytokine HMGB1 promotes ALI by inducing AEC necroptosis, and its underlying mechanisms remain elusive. Here, a prospective cohort study was carried out, in which plasma samples from 21 CPB patients were isolated at four specific time points: pre-CPB, 2, 12, and 24 h after initiation of CPB. Plasma exosomes were extracted via ultra-high-speed centrifugation and cocultured with AEC cell line-A549 cells at increasing concentrations of 50, 100, and 150 μg/mL. Then, HMGB1 antagonist-Box A and mtDNA deficiency ethidium bromide (EtBr) were applied to explore the underlying role of exosomal HMGB1 and cytoplasm mitochondrial DNA in AEC. Western blot analysis showed that plasma exosomal HMGB1 expression gradually increased and peaked at 24 h after CPB. Twenty-four–hour treatment of CPB-derived exosomes at 150 μg/mL for 24 h could induce necroptosis by promoting mitochondrial fission and further elevating cytoplasm mtDNA levels in A549 cells, which was successfully blocked by Box A or EtBr. Most importantly, EtBr significantly inhibited cytoplasm mtDNA downstream guanosine monophosphate (GMP)-AMP synthase (cGAS)/stimulator of interferon gene (STING) signal pathway. Collectively, these data demonstrate that CPB-derived plasma exosomal HMGB1 contributes to AEC necroptosis through the mtDNA/cGAS/STING pathway.